Effect of sous vide cooking and ageing on tenderness and water-holding capacity of low-value beef muscles from young and older animals. (May 2021) - Naqvi, Zahra B.; Thomson, Peter C.; Ha, Minh; Campbell, Michael A.; McGill, David M.; Friend, Michael A.; Warner, Robyn D.
Abstract: This study investigated the effect of the age of the animal, sous vide cooking and ageing on tenderness and water-holding capacity of bovine biceps femoris (BF) and semitendinosus (ST). Samples of each muscle from young (<18 months) and older (30–42 months) animals, at 0 and 13 days ageing, were cooked at 55 °C, 65 °C, and 75 °C for 1 h, 8 h and 18 h and tested for Warner-Bratzler shear force (WBSF), cooking loss, total water content and collagen solubility. WBSF reduced with ageing ( P  < 0.05) and sous vide cooking ( P  < 0.001) in both muscles. Our results demonstrated that meat from older animals required a higher temperature (75 °C) and prolonged cooking (18 h) to achieve equal tenderness in both BF and ST relative to young animals. Cooking time, temperature and their interaction altered cooking loss ( P  < 0.001) for both muscles. The higher cooking temperature increased collagen solubility ( P  < 0.001) in both muscles and solubilisation of collagen may have contributed to improved tenderness of BF and ST in sous vide cooking.